DFT study of Mn-doped CeO2: The structural and electronic properties - Ali, Aqeel; Nooraldeen A. Toama (University of Thi-Qar Journal of Science, 2024)
The structural and electronic characteristics of manganese doped cerium oxide are investigated by means of the density functional theory with Habbard parameter approach. Experimental evidence and other theoretical findings corroborate the computed electronic characteristics, bulk modulus, cell volume, and equilibrium lattice parameter for ceria. By replacing the Ce atom with Mn, the bond length, bulk modulus, cell volume, and lattice parameter are all reduced. In the meantime, we see a narrowing of the band-gap. Interestingly, it is seen that the strength of the oxygen occupied states to cerium empty states transition and the covalent nature of the cerium oxygen bond are both reduced when manganese is doped into ceria. The heavy manganese doped ceria system may be used for applications involving the spin dependent current and light absorption, since it exhibits steeper absorption peaks spanning from 3.0 to 3.44 eV of spin down and spin upper, respectively.